2013
DOI: 10.21082/ijas.v11n1.2010.p11-15
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Agronomic Characters and Grain Yield of Rice for Tidal Swamp Areas

Abstract: Development of rice varieties for tidal swamp areas is emphasized on the improvement of rice yield potential in specific environment. However, grain yield is a complex trait and highly dependent on the other agronomic characters; while information related to the relationship between agronomic characters and grain yield in the breeding program particularly for tidal swamp areas is very limited. The objective of this study was to investigate relationship between agronomic characters and grain yield of rice as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 3 publications
4
23
0
3
Order By: Relevance
“…This indicated that these traits were mainly controlled by genetic factors, while the environmental factors play minor role in the explanation of these traits. Similar results were recorded previously by Cruz et al (2008), Hairmansis et al, (2010), Abarshahr et al, (2011), Sohrabi et al, (2012, Vanisree et al, (2013) and Premkumar et al, (2016).…”
Section: Genotypic and Phenotypic Correlationsupporting
confidence: 92%
“…This indicated that these traits were mainly controlled by genetic factors, while the environmental factors play minor role in the explanation of these traits. Similar results were recorded previously by Cruz et al (2008), Hairmansis et al, (2010), Abarshahr et al, (2011), Sohrabi et al, (2012, Vanisree et al, (2013) and Premkumar et al, (2016).…”
Section: Genotypic and Phenotypic Correlationsupporting
confidence: 92%
“…Ullah et al (2011) detected that grain yield was positively and significantly associated with panicle length and grains per panicle. Hairmansis et al (2010) also recorded a positive and significant association of grain yield with filled grains per panicle, spikelets per panicle and spikelet fertility.…”
Section: Introductionmentioning
confidence: 87%
“…Grain yield is a complex trait and highly dependent on the other agronomic characters (Hairmansis et al, 2010). All possible correlations among the different characters for each location were measured (Table 5).…”
Section: Correlation and Path Analysismentioning
confidence: 99%